Investment Arbitration: On The Availability of the State Counterclaim - Maarif, Syamsul; Mustofa, Latif; Husni, Alfi (UI Scholars Hub, 2026)
This paper explores the availability and significance of state counterclaims in international investment arbitration, a mechanism typically perceived as favoring investors. While investor-state dispute settlement (ISDS) provides foreign investors with powerful legal recourse, it has led to concerns over the asymmetry in investor-state relations, often perceived as skewed against host states. By allowing states to file counterclaims, a more balanced and sustainable arbitration framework can be achieved, discouraging baseless claims and promoting fairness. The analysis draws on arbitration rules of major tribunals, including the ICSID and UNCITRAL frameworks, and reviews notable cases such as Metal-Tech v. Uzbekistan, Al-Warraq v. Indonesia, and Perenco v. Ecuador to illustrate how tribunals handle state counterclaims and the associated legal hurdles. The paper emphasizes that for a counterclaim to be admitted, it must align with the agreement to arbitrate, meet jurisdictional requirements, and be supported by the applicable treaty’s provisions. The research concludes that while state counterclaims are theoretically permissible under current arbitration rules, their practical application remains constrained by treaty language and procedural norms. Allowing counterclaims more explicitly could deter opportunistic claims by investors and foster a more equitable ISDS system.